(Invited) Non-Volatile Resistive Memory: Technology Capable of Revolutionary Compromises. (26th April 2016) - Navarro, Gabriele; Vianello, Elisa; Sousa, Véronique; Molas, Gabriel; Nowak, Etienne; De Salvo, Barbara; Perniola, Luca
Abstract : Non-Volatile Resistive Memory (NVRM) such as Phase-Change Memory, Oxide-based Memory and Conductive Bridging Memory has rapidly increased in maturity in the last decade. In a memory market context dominated by DRAM and Flash technologies, the evolving memory hierarchy and the strong differentiation of the applications portfolio represent a real opportunity for NVRM to emerge. The real revolution of this technology resides in its versatility made possible by general trade-offs existing between the different NVRM performances, highlighted in the last years by the research and the development in several fields (e.g. materials science, engineering, etc.). We present here some of these trade-offs, and how they can be used to target specific applications.